SOCIO-ECONOMIC IMPLICATIONS FOR SWAMP RECLAMATION IN ABONNEMA, NIGERIA - Michael. Didia; Stewart.S. Owukio (American Journals, 2022)
Abonnema, a riverine domain is a large town in the Kalabari Kingdom in Akuku-Toru Local Government Area Rivers State, Nigeria is surrounded by water; the town is located in the southwest of Rivers State founded in 1882, with a population of 74468. Abonnema keyed into land reclamation because of its overcrowded condition and to satisfy the need for new homes. This research was aimed at evaluating the positive and negative implications of swamp reclamation on livelihood and infrastructural delivery in Abonnema. In this study, field observations, questionnaire surveys, land-sat imageries, and sky-view lifetime drone photographs were achieved from the Rivers State Ministry of Works and perspective. Supervised classification of the image processing was adopted to determine the percentage of land cover in the study area. Findings showed that land reclamation activities have caused the destruction and displacement of organisms and species; and on the other hand, most populations have benefited from land reclamation activities. These advantages include the development of infrastructure and access to employment opportunities, an extension of land capacity, improved living standard for citizens. The study, therefore, recommends that the Rivers State Government should not relent on reclaiming more land, especially in other islands in Rivers State, so such islands will experience the benefits of infrastructural development and the State Government should also put in place more laws and strategies to regulate reclamation activities across the state. Educational organizations should also carry out environmental awareness and perception of the environment, as part of their duty.
Keywords: Swamp reclamation; Abonnema; Wetlands